Low-Cost Light Sensor-Based Physics Experiments: Enhancing Students’ Experimental Skills - Hadi, Muhammad Irzha; Aimran, Wan Mohm; Prasitpong, Singha (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The purpose of this study is to examine the effectiveness of a simple light sensor-based experiment in improving students’ experimental skills in physics learning, particularly in the topic of optics, among eleventh-grade vocational high school students. Methodology: This study used a quantitative experimental method with a one-group design. The tools included a simple light sensor based on an LDR, breadboard, resistors, LED, buzzer, and multimeter. Data were collected through observation sheets, product assessment, and student response questionnaires. Data analysis was conducted using IBM SPSS Statistics software. Main Findings: Students’ experimental skills reached a high level with a mean score of 81.61, significantly exceeding the Minimum Completeness Criteria score of 75 (p < 0.05). All students successfully completed the simple light sensor experiment. Skill indicators showed an overall average of 86.67. Student responses to the media and learning process were very positive, with mean percentages of 87.07% and 86.90%, while product evaluation by teachers and observers reached 100%. Novelty/Originality of this study: This study provides new empirical evidence on the effectiveness of low-cost, simple light sensor (light dependent resistor)-based experiments in real vocational classrooms, focusing on direct measurement of students’ science process skills. It advances existing knowledge by demonstrating that affordable, hands-on experimental media can significantly enhance practical skills and learning engagement in physics education contexts with limited laboratory resources.